Gugatan Perwakilan Kelompok (Class Action) tentang Pencemaran Air Pada Sungai Kalundang - Dela Meilany (Program Studi Ilmu Hukum, Universitas Kuningan, 2024)
Water pollution is an event caused by the entry of living things, substances, energy or other elements into water in the form of gas, dissolved substances and particles, so that it can cause damage to the water, polluting the quality of the water and disrupting its function. This study aims to analyze legally and based on the Decision of the Rantau Prapat District Court Number 15 / Pdt.G / LH / 2023 / PN.RAP. The research method used in this study uses a normative method, namely the rules of literature study, namely collecting and conducting studies of several library sources. The results of the study are that the Plaintiff's Lawsuit was declared invalid. The Plaintiff does not have legal standing in accordance with Article 5 paragraph 3 of the Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2002 concerning Class Action Lawsuits and other laws and regulations. The conclusion of the Class Action Lawsuit must be based on the Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2002 concerning Class Action Lawsuits. Advice for every plaintiff to understand the applicable laws and regulations so that future Class Action Lawsuits can be accepted.